Layanan Ekstensi di Dinas Kearsipan Dan Perpustakaan Kabupaten Trenggalek - Yanuarita, Heylen Amildha (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Public service is one manifestation of the function of the state apparatus as a public servant, public service is intended for the welfare of society or citizens. Professional public service means public service characterized by accountability and responsibility from service providers (government officials). This research aims to find out how mobile library services are at the Archives and Libraries Office of Trenggalek Regency. The research method used in this study is a qualitative descriptive method and data collection techniques through observation, in-depth interviews with informants, and documentation. The results of the study show that mobile library services at the Trenggalek Regency Archives and Libraries Service are good. This is influenced by several factors that affect services with the lack of available facilities and infrastructure, especially books that are not updated according to the needs of the community as well as the lack of use of technology so that during a pandemic, the mobile library program could not run.